1995
DOI: 10.1002/jor.1100130520
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte response to particulate biomaterials generated in vivo and in vitro

Abstract: We studied the ability of four clinically relevant particle species to stimulate human peripheral blood monocytes to release bone-resorbing agents, including interleukin-1 (both interleukin-1 alpha and interleukin-1 beta), interleukin-6, and prostaglandin E2. The species studied were titanium-6% aluminum-4% vanadium (TiAlV), commercially pure titanium, fabricated ultrahigh molecular weight polyethylene, and polyethylene retrieved from interfacial membranes of failed uncemented total hip arthroplasties. For all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
194
4
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 256 publications
(215 citation statements)
references
References 39 publications
14
194
4
3
Order By: Relevance
“…An additional factor relates to the marked variability in the particulate test materials and specific culture conditions. Numerous investigators have shown that particle size, shape, surface roughness, relative hydrophobicity or hydrophilicity and composition, are critical factors in defining the consequences of particle-cell interactions [38,35,40,49,52,56]. When these properties are compared in different studies, it is clear that there is marked heterogeneity in the materials that are being evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional factor relates to the marked variability in the particulate test materials and specific culture conditions. Numerous investigators have shown that particle size, shape, surface roughness, relative hydrophobicity or hydrophilicity and composition, are critical factors in defining the consequences of particle-cell interactions [38,35,40,49,52,56]. When these properties are compared in different studies, it is clear that there is marked heterogeneity in the materials that are being evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The particles were washed three times in excess PBS and resuspended in PBS. Heat i/zurrirution: Following three washes in 70% ethanol as stated previously, the particles were autoclaved for I h and subsequently heated in a baking oven at 175 "C for 3 h [47]. following which the particles were resuspended in PBS.…”
Section: Dosage Cfpmriandsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, methods developed to assess the biologic reactivity to wear debris have considered the sizes, compositions, and surface areas of the particles [22,30,33,44,45]. However, a careful reevaluation of the biologic activity for crosslinked PE should take into account the overall volume in addition to the particle size, composition, and area and should be based on a highly precise method for obtaining purified and well-characterized PE particles.…”
Section: Introductionmentioning
confidence: 99%